2012
DOI: 10.1088/0964-1726/22/1/015020
|View full text |Cite
|
Sign up to set email alerts
|

Integration and road tests of a self-sensing CNT concrete pavement system for traffic detection

Abstract: In this paper, a self-sensing carbon nanotube (CNT) concrete pavement system for traffic detection is proposed and tested in a roadway. Pre-cast and cast-in-place self-sensing CNT concrete sensors were simultaneously integrated into a controlled pavement test section at the Minnesota Road Research Facility (MnROAD), USA. Road tests of the system were conducted by using an MnROAD five-axle semi-trailer tractor truck and a van, respectively, both in the winter and summer. Test results show that the proposed self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…For instance, Han et al [ 4 ] installed mortar sensing blocks in a test pavement using 1.0 wt % multi-walled carbon nanotubes (MWNT) for traffi c fl ow monitoring. While this study demonstrated the possibility of using this technology in real-world conditions, future applications would require self-sensing cementitious composites to be larger and fabricated at lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Han et al [ 4 ] installed mortar sensing blocks in a test pavement using 1.0 wt % multi-walled carbon nanotubes (MWNT) for traffi c fl ow monitoring. While this study demonstrated the possibility of using this technology in real-world conditions, future applications would require self-sensing cementitious composites to be larger and fabricated at lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier [24], [25], the change in electrical resistivity of the QTC sensors caused by vehicular passing is the same as that in electrical resistance, which is equal to the change in electrical voltage signal, i.e.,…”
Section: Measurementmentioning
confidence: 81%
“…As a sequence of vehicles pass over the sensors, the curve produces a corresponding sequence of peaks. Vehicle count (25) and unit time traffic load (about 5 per minute) can be simply achieved from the output curve. The correct rate of vehicle count is 100%, which is validated by the video record on the scene.…”
Section: E Real-time Traffic Detectionmentioning
confidence: 99%
“…They found that vehicular loads can lead to remarkable changes in the electrical resistance of carbon nanotube cement-based materials in self-sensing pavements, so traffic flow monitoring and even possible identification of different vehicular loadings could be realized by measuring the electrical resistance of the composites. Han et al recently extended their previous work on self-sensing carbon nanotube concrete pavements with intensive road tests [35]. They integrated self-sensing carbon nanotube concrete into a controlled pavement test section at the Minnesota Road Research Facility to build a self-sensing concrete pavement system for traffic detection.…”
Section: Applications Of Self-sensing Concrete 217mentioning
confidence: 99%
“…Road test results showed that the proposed self-sensing pavement system accurately detected the passage of different vehicles under different vehicular speeds and test environments. The developed self-sensing carbon nanotube concrete pavement system could achieve real-time vehicle flow detection with a high detection rate and low false-alarm rate [35]. Han et al also designed another type of self-sensing pavement for vehicle detection [36].…”
Section: Applications Of Self-sensing Concrete 217mentioning
confidence: 99%